Soil C Sequestration as a Biological Negative Emission Strategy - Paustian, Keith; Larson, Eric; Kent, Jeffrey; Marx, Ernie; Swan, Amy (Frontiers in Climate, 2019)
Soil carbon (C) sequestration in one of three main approaches to carbon dioxide removal and storage through management of terrestrial ecosystems. Soil C sequestration relies of the adoption of improved management practices that increase the amount of carbon stored as soil organic matter, primarily in cropland and grazing lands. These C sequestering practices act by increasing the rate of input of plant-derived residues to soils and/or by reducing the rates of turnover of organic C stocks already in the soil. In addition to carbon dioxide removal potential, increases in soil organic matter/soil C content are highly beneficial from the standpoint of soil health and soil fertility Practices to increase soil C stocks include well-known, proven techniques or “best management practices” (BMP) for building soil carbon. A second category includes what we refer to as frontier technologies for which significant technological and/or economic barriers exist today, but for which further R&D and/or economic incentives might offer the potential for greater sequestration over the longer term. We reviewed published estimates of global soil carbon sequestration potential, representing the biophysical potential for managed cropland and/or grassland systems to store additional carbon assuming widespread (near complete) adoption of BMPs. The majority of studies suggests that 4 to 5 GtCO2/y as an upper limit for global biophysical potential with near complete adoption of BMPs. In the longer-term, if frontier technologies are successfully deployed, the global estimate might grow to 8 GtCO2/y. There is a strong scientific basis for managing agricultural soils to act as a significant carbon (C) sink over the next several decades. A two-stage strategy, to first incentivize adoption of well developed, conventional soil C sequestering practices, while investing in R&D on new frontier technologies that could come on-line in the next 2-3 decades, could maximize benefits. Implementation of such policies will require robust, scientifically-sound measurement, reporting, and verification (MRV) systems to track that policy goals are being met and that claimed increases in soil C stocks are real.